A Review of Financial Literacy in Southeast Asian Cognate Countries - Endang Komesty Sinaga; Ikaputra Waspada (Journal of Management and Business Review, 2023)
A cashless society is a collective vision of world citizens to create a payment system that is faster, more flexible, and more automatic. This study aims to formulate findings on publications conducted in 2012-2022, focusing on a cashless society. Using the Systematic Literature Review approach, this study uses 14 main sources from the Scopus database to identify shared understanding, supporting factors, and the impact of a cashless society from the perspective of researchers. This study found that the formation of a cashless society is a solution for efforts to grow the economy and speed up societal transactions. Another benefit is the prevention of criminal acts of corruption, extortion, and fraud, where electronic payments made in a registered manner have suppressed these crimes. The dark side of a cashless society is the potential for privacy violations and paralysis of the economic system caused by internet system failures